A note on poverty in Kosovo - Sumon Kumar Bhaumik; Ira N. Gang; Myeong-Su Yun (Rutgers University, Department of Economics, 2005)
Kosovo is a war-torn corner of the former Yugoslavia, where a civil war between ethnic Albanians and ethnic Serbs raged during most of the 1990s. We examine the incidence and depth of poverty and some of its correlates in post-conflict Kosovo using the Living Standards Measurement Survey.
Keywords: I32; O12; J15; 330; Poverty; ethnicity; transition